EDUKASI PEMILAHAN SAMPAH DENGAN MEDIA INTERAKTIF PADA SISWA KELAS 1 SD NEGERI PENANGGUNGAN: WASTE SORTING EDUCATION WITH INTERACTIVE MEDIA FOR 1ST GRADE STUDENTS OF SD NEGERI PENANGGUNGAN - Safitri Nur Ramadhani; Aileena Solicitor Costa Rica El Chidtian (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Waste problems are often encountered in the surrounding community. Penanggungan Village is one of the tourist villages located in Trawas District, Mojokerto Regency. Environmental cleanliness is certainly in the spotlight because many tourists visit the village. In minimizing littering, it is necessary to provide early education about waste sorting, especially for elementary school students. Through community service activities, Bina Desa Trawas of MBKM Universitas Pembangunan Nasional "Veteran" Jawa Timur conducted teaching activities for grade 1 students of SD Negeri Penanggungan. Learning activities are carried out using interactive media in the form of board games about waste sorting. In addition to interactive board game media, learning activities also use supporting media such as animated videos.